RESPON TANAMAN KARET TERHADAP PEMBERIAN ETEPON DAN WAKTU SADAP YANG BERBEDA - Yatmin Yatmin; Krisnarini Krisnarini (STIPER Dharma Wacana Metro, 2014)
Natural latex is an agricultural product that has a lot of benefits human needs. The efforts to increase latex production have to be continually done in order to meet the requirement. Paying attention to the time of latex taking and giving latex stimulant treatment are the important efforts. Both the efforts have to be taken care very well to prevent the damage on the coutchouc. The objective of the study is to know the effect of applying ethepon and the time of latex taking to word latex production on the coutchouc and the interaction between both of the factors. The research took place in Dharma Agung Village sub-distric of Seputih Mataram, Central Lampung regency on May—July, 2013. The ingredients used in the research are: coutchouc clone PB 260, ethepon with Cepha 100 PA brand (1,5% and 2,5% of concentration), acetic acid and aquades. The research is in factorial pattern which is arranged in complete randomized block design by three repetitions. The first factor is the application of ethepon (A) divided into three treatments: non ethepon application (a1), ethepon application with 1,5% concentration (a2), and ethepon application with 2,5% concentration (a3). The second factor is the time of latex taking (T) at 05.00 a.m. (t1), at 07.00 a.m. (t2), and at 09.00 a.m. (t3). Based on the finding of the research, it can be concluded that the use of ethepon with 2,5% concentration and the earliest time latex taking (at 05.00 a.m.) produce the highest amount of latex than others treatments.Keywords: Latex, Ethepon, Latex Taking Time